2008
DOI: 10.1016/j.amjmed.2007.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Delays in Seeking Medical Care in Hospitalized Patients with Decompensated Heart Failure

Abstract: The results of this study in residents of a large New England metropolitan area suggest that patients hospitalized with acute heart failure exhibit considerable delays in seeking medical care. Several demographic and clinical characteristics were associated with prolonged delay. More research is needed to better understand the reasons why patients with this serious and increasingly prevalent clinical syndrome delay seeking medical care in a timely fashion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 22 publications
6
55
0
Order By: Relevance
“…Furthermore, it is often difficult for chronic HF patients to differentiate between baseline symptoms and signs of deterioration. 26 Gender was independently associated with patient delay, which has also been reported in another study 9 ; male patients were more likely to delay in seeking care. This result was found for all patients, as well for patients with a history of HF.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Furthermore, it is often difficult for chronic HF patients to differentiate between baseline symptoms and signs of deterioration. 26 Gender was independently associated with patient delay, which has also been reported in another study 9 ; male patients were more likely to delay in seeking care. This result was found for all patients, as well for patients with a history of HF.…”
Section: Discussionsupporting
confidence: 53%
“…Although delay in HF patients has been studied previously [6][7][8][9][10] , these studies actually assessed pre-hospital delay ( Figure 1). However, little is known on patient delay as we defined earlier as the 4 time from worsening symptoms to actually contacting a health care provider, which reflects the patients' own action in seeking care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In prior studies, edema was identified as one of the most common symptoms that contribute to a delay in seeking care, 4,13) and it predicted a two-fold risk of increased delay. 14,15) On the basis of these fi ndings, we decided to examine if the patients sought care when their feet/legs became more swollen.…”
Section: Methodsmentioning
confidence: 99%
“…As shown in the multi-centre study by Goldberg et al (2008), medical chart information collected on care-seeking delay behavior data was missing for 56% of the sample. {{4127 Goldberg, Robert J.…”
Section: Interventions and Other Health System Encountersmentioning
confidence: 99%